No relevant associations between markers of smoking behaviour and plasma progesterone concentrations: findings from a sex-stratified cohort study - Gihl, Julia; Zacharias, Norman; Hoffmann, Sabine; Thürauf, Norbert; Schaller, Gerd; Winterer, Georg; Koopmann, Anne; Kiefer, Falk; Kornhuber, Johannes; Mühle, Christiane; Lenz, Bernd (Addiction biology, 2025)
Cigarette smoking is a prevalent and critical global health issue, with inconsistent findings for its effects on endogenous progesterone concentrations. This large multicentre study investigated the associations between various markers of smoking behaviour and plasma progesterone concentrations using a sex-segregating approach. We studied 747 males aged 18-65 years and 158 peri−/postmenopausal females aged 50-65 years and assessed differences in plasma progesterone concentrations between smokers and never-smokers and associations of plasma progesterone concentrations with the Fagerström Test for Nicotine Dependence (FTND) score, cigarette pack years, age at onset of regular smoking, number of cigarettes smoked daily, exhaled carbon monoxide (CO), plasma cotinine and the Questionnaire of Smoking Urges (QSU) score. In models adjusted for age, body mass index (BMI), years of education, Alcohol Use Disorder Identification Test (AUDIT) scores, intake of any medication and study centre, and after correction for multiple hypothesis testing, there were no significant differences in plasma progesterone concentrations between smokers and never-smokers, and no significant associations between any of the mentioned markers of smoking behaviour and plasma progesterone concentrations in either males or females. The results suggest that smoking behaviour has no substantial effect on plasma progesterone concentrations and is not an important confounder in studies investigating progesterone.